Je suplementace kalcidiolu při chronických onemocněních ledvin přínosná, nebo riziková? - Okša, Adrian; Spustová, Viera; Krivošíková, Zora; Gazdíková, Katarína; Fedelešová, Viera; Lajdová, Ingrid; Štefíková, Kornélia; Bernasovská, Gabriela; Žilinská, Zuzana; Dzúrik, Rastislav (Postgraduální nefrologie, 2009)
Data on the efficacy and safety of long-term vitamin D supplementation in chronic kidney disease (CKD) are scarce. We assessed the effects of the 12-month vitamin D(3) treatment on mineral metabolism and calciotropic hormones in patients with CKD stages 2-4. METHODS: Eighty-seven patients (mean age 66 years, men/women 33/54) were randomized to cholecalciferol treatment with either 5,000 or 20,000 IU/week. Serum calcium, phosphate, 25(OH)D(3), 1,25(OH)(2)D(3), PTH and urinary mineral concentrations were obtained at baseline and after 4, 8 and 12 months. RESULTS: The median serum mineral concentrations were normal and not changed throughout the study. The number of hypercalciuric patients slightly increased with higher dose, but no sustained rise in calciuria was present. Vitamin D insufficiency/deficiency was revealed in 72 (83%) patients at baseline and 37 (43%) at month 12. The 25(OH)D(3) levels increased more with higher dose; a rise in 1,25(OH)(2)D(3) was less impressive. The parathyroid hormone (PTH) concentrations were reduced, but the number of subjects with PTH below the lower limit for CKD stage 3 increased equally with both doses. CONCLUSIONS: Vitamin D insufficiency/deficiency in CKD significantly improved after the 12-month cholecalciferol treatment, with higher dose being more effective and equally safe. Further studies of vitamin D(3) effects on bone metabolism are warranted. Copyright 2008 S. Karger AG, Basel.
Keywords: nemoci ledvin; Female; ženské pohlaví; Dietary Supplements; lidé; Hormones; nedostatek vitaminu D; potravní doplňky; Kidney Diseases; Minerals; Cholecalciferol; Male; cholekalciferol; Aged; Vitamin D Deficiency; minerály; chronická nemoc; hormony; senioři; mužské pohlaví; Chronic Disease; Humans